DEVELOPMENT OF PREDICT-OBSERVE-EXPLAIN (POE) BASED AUTHENTIC PROBLEMS"™ INSTRUCTIONAL PACKAGE TO IMPROVE STUDENTS"™ CRITICAL THINKING SKILLS - Noor, Aulia Fauzan; Yunus, Rahmat; Suyidno, Suyidno; Fahmi, Fahmi (Jurnal Pendidikan Matematika dan IPA, 2023)
Science instruction is required to be able to develop critical thinking skills and solve various authentic problems. However, based on the preliminary study results, the science learning process does not emphasize the development of critical thinking skills. Therefore, this study aims to produce appropriate POE (Predict-Observe-Explain) based authentic instructional package that are valid, practical, and effective to improve students' critical thinking skills. This research is educational development research using Tessmers' development model, which includes self-evaluation, expert test, individual test, small group test, and field test. The subjects of the research trial were eight students of class VIIIE and 29 students of class VIIIF of SMPN 33 Banjarmasin. The research data were obtained by expert testing on assessment using validation instruments, observations on practicality assessment using RPP implementation instruments, and tests on effectiveness assessment using critical LP instruments. The results of the data were analyzed quantitatively and qualitatively and the results obtained that the learning tools were categorized as very valid, practical, and effective. Therefore, a POE (Predict-Observe-Explain) based authentic problem instructional package is feasible to improve students' critical thinking skills.